Assessment Of Knowledge and Attitude on Family Life of Adolescent Girls - Inamdar, Madhuri; Inamdar, Sameer; Khan, Yasmeen Z (National Journal of Community Medicine, 2014)
Background: At adolescence, health behaviors are formed and life courses are charted. Limited knowledge about family life leaves adolescent girls vulnerable to increased risks from sexual exploitation, pregnancy, and violence. Methods: A qualitative cross sectional study of girls aged between 12 and 18 years, from schools and slums. Results: The knowledge about Child marriage Act (OR=52.2, CI=141.1, 19.31) and legal rights of women (OR=26.13, CI=75.80, 9.005) was significantly higher (P< 0.001) among school going girls. The age of onset of puberty and prior knowledge of menstruation was better known by non-school going adolescents (p<0.001). Out of the total 1000 adolescent girls, only 391 had heard about STDs (p<0.001) and 201 had heard about reproductive health (p<0.001).The difference is statistically significant regarding number of children required per family (OR=1.92, CI=3.459, 1.065), mechanism of pregnancy (OR=2.59, CI=4.659, 1.440) and the fact that sex education is not a danger for our culture (OR=2.296, CI=4.187, 1.259). Only 13.6% girls received sex education (p<0.001, OR=2.71, CI=4.911, 1.496).They agreed with the fact that son is not essential for family (p<0.001). Conclusion: With awareness and understanding about their bodies, emotional and physical capacities, and the legal aspects of family formation, adolescent girls will have a positive and stable family life and a better quality of life.